Development and Validation of A Reversed Phase-HPLC-DAD Method for Determination of Bisphenol-A in Artificial Saliva - DEMIRKAYA, FATMA; KADIOGLU*, YUCEL (Asian Journal of Chemistry, 2009)
Bisphenol-A is one of estrogenic xenobiotics present as an impurity in dental sealants and composites based on dimethacrylate monomers. In this study, bisphenol-A in artificial saliva was analyzed by simple, accurate, precise and sensitive reversed phase HPLC-DAD method requiring simple sample preparation. Bisphenol-A separated by the reversed-phase C18 column using simple the mobile phase containing isocratic mixture of acetonitrile-Milli-Q grade water (50:50 v/v) at flow rate of 1 mL min-1. Linearity has been obtained in the range of 0.5-30 μg mL-1, whereas limit of detection and limit of quantification are 0.01 and 0.02 μg mL-1, respectively. Both intra day and inter day precision showed acceptable RSD values were lower than < 6.3 % and < 9.5 %, respectively. The recovery of developed method was also between 96.8-105.9 %. It was suggested that proposed method has been successfully applied in routine analysis of bisphenol-A in saliva after dental treatment.